Effect of temperature on land use changes from forest to oil palm in Sabah / Asma' Amalina Md Yusof - Md Yusof, Asma' Amalina (2018)
The oil palm plantation has often been accused as the cause of global warming. The impact of oil palm expansion has been particularly severe in tropical forest regions and oil palm plantation is expected to increase continuously over the next 10 or 20 years. The aim of this study is to analyses the pattern of oil palm distribution and how its effect the temperature in Sabah from year 2000 to 2016. Landsat satellite images data were obtained from the USGS website of available years from 2000 to year 2016. These data were mosaicked and classified by using ERDAS Imagine 2014 and ArcGIS software. The result for area of changes of oil palm is about 17721.28 km2 from 12601.91 km2 in year 2000 to 29823.19 km2 in year 2016. Then, the pattern of changes of oil palm distribution was analyzed by using Moran’s I Spatial Autocorrelation method. The result obtained for the distribution pattern is random distribution. Meanwhile, the relationship between LST and the oil palm expansion was conducted by using correlation analysis. The result has shown that the R2 is not linearly increase, however in 2016 the R2 is quite high which is R2 = 0.34. In conclusion, it can be conclude that the oil palm expansion have impact the land surface temperature, however several factors should be more investigated further. Assumption of the age of oil palm is one of the factor, but validation on the site is also important.